Strength development and microstructural behavior of soils stabilized with palm oil fuel ash (POFA)-based geopolymer - Khasib, Isam Adnan; Nik Daud, Nik Norsyahariati; Mohd Nasir, Noor Azline (MDPI AG, 2021)
Using geopolymer in soil stabilization has gained much attention recently due to its efficiency in improving soil properties and being environmentally friendly at the same time. This research aims to investigate the effect of palm oil fuel ash (POFA)-based geopolymer on soft soil stabilization. The mechanical and microstructural performance of two types of clay soil treated with geopolymer produce from POFA material was the focus of this study. In this respect, a series of unconfined compression and direct shear tests were conducted to investigate the mechanical properties of soils treated with POFA-based geopolymer. Furthermore, the microstructural changes in the treated samples were analyzed using field emission electron microscopy (FESEM) and energy dispersive X-ray (EDX). In accordance with the results, it was indicated that the shear strength of both soils soared by increasing the dosage of POFA-based geopolymer. Geopolymer with 40% POFA of the dry weight of soils yielded the highest UCS value at both curing periods, 7 and 28 days. Furthermore, the microstructural analysis revealed material modifications (N-A-S-H gel formation) related to strength enhancement. These results suggest the potentiality of using a POFA-based geopolymer binder to stabilize soft soil.